Nepal : Public Expenditure Review, Volume 4. Transport Sector - World Bank (Washington, DC, 2013)
The report is an overview of Nepal's economic development, comprising five volumes, which include the main report, followed by reviews on agricultural and rural development, on the social sectors, and, the transport sector. Although development progress is noteworthy in many areas, considerable evidence of improper resource spending exist, thus, the main objective of this report is to identify the incentives, and institutional factors that contributed to this spending, and propose recommendations. Systemic factors have consistently hindered implementation, and development results, such as deficient budget planning, resource allocation, and expenditure management, coupled with the lack of ownership of projects, and programs which contributed to poor performance. Institutional weakness, and governance issues remain the most critical aspects affecting effectiveness of public spending across sectors in Nepal. The report suggests that traditional budget reforms alone, will not be effective to improve public resource management, rather, changes in the political environment, and institutional capacity are required, prior to the much needed reforms. Given the fiscal constraints, the government should promote private participation to undertake economic activities, and, further enhance and promote, public involvement in social sectors development, and greater local ownership of public expenditure programs.